Cutting Edge: Unusual NK Cell Responses to HIV-1 Peptides Are Associated with Protection against Maternal-Infant Transmission of HIV-1 - Tiemessen, Caroline T. (2009)
Most infants exposed to HIV-1 in utero and at delivery do not acquire infection. We show that mothers and infants who have CD3-negative cells that respond to HIV-1 peptides are substantially less likely to transmit and acquire infection, respectively. The CD3-negative cells, shown to be NK cells, respond with remarkable specificity and high magnitude to HIV-1 peptides from Env (envelope) and Reg (regulatory) protein regions, as measured by a whole blood intracellular cytokine assay only in the context of HIV-1 infection or exposure. These findings identify an important new measure of protective immunity to HIV-1 that highlights the importance of innate immunity in preventing the establishment of HIV-1 infection.